Síntese de nanopartículas superparamagnéticas de ferrita de cobalto (CoFe2O4): uma nova metodologia - Abreu, Maria Karolina da Silva Oliveira (2025)
Comprehending the processes involved in the synthesis of magnetic nanoparticles (NPs) is crucial for developing a rapid and reproducible synthetic method for producing nanometric scale materials. Nonetheless, finding a synthesis methodology that facilitates the rapid, reliable production of nanoparticles with a uniform size distribution remains challenging. This work provides a new synthetic approach using the hydrothermal method for producing CoFe2O4 NPs in a single step utilizing microwave radiation, assuring homogeneity in the size distribution in addition to improving magnetic properties. The introduction of natural polymers as reducing agents to mitigate the environmental impact combined with microwave radiation to accelerate the process created new NP production possibilities. This study investigated how solvent, surface agent concentration, and reducing agent type affected NP size, crystallinity, magnetism, and colloidal stability. Nine samples were produced, exhibiting X-ray diffraction patterns coincident with the CoFe2O4 phase in a cubic system. The change in the constituents of the reaction media led to a variation in the diameter of the nanoparticles from 6 to 30 nm. The analysis of the magnetic properties revealed the acquisition of superparamagnetic nanoparticles at room temperature, exhibiting saturation magnetization (MS) values from 40 to 85 emu g-1. It is worth noting that nanoparticles produced with carboxymethylated cashew gum (GCCM) presented a MS value of 85.5 emu g-1, showing minimal magnetic dilution following polymer coating. The dynamic light scattering results indicated the formation of NPs resistant to agglomeration in aqueous medium (ζ = ± 30 mV), enabling cytotoxicity and hyperthermia experiments in biological medium. While the CFO-R-75-EG and CFO-R-150-EG samples demonstrated potential for use in magnetic hyperthermia tests, preliminary data indicated that the CFO-GCCM-150-EG NPs did not exhibit toxicity when exposed to zebrafish.